2020
DOI: 10.1001/jamasurg.2020.3318
|View full text |Cite
|
Sign up to set email alerts
|

Association of Race, Health Insurance Status, and Household Income With Location and Outcomes of Ambulatory Surgery Among Adult Patients in 2 US States

Abstract: The receipt of surgery in freestanding ambulatory surgery centers (ASCs) is often less costly compared with surgery in hospital-based outpatient departments. Although increasing numbers of surgical procedures are now being performed in freestanding ASCs, questions remain regarding the existence of disparities among patients receiving care at ASCs. OBJECTIVE To examine the association of patient race, health insurance status, and household income with the location (ASC vs hospital-based outpatient department) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…While there are no previous studies on the socioeconomic patient characteristic differences between inpatient or outpatient care for pediatric SCHF patients, recent studies on total hip and total knee arthroplasties have emphasized that higher SDI scores are associated with inpatient care, alongside African American race, and existence of comorbidities [ 16 , 24 ]. More specifically, a recent study of adult ambulatory surgical care in New York also reported that Black and Hispanic patients had higher odds of receiving inpatient care [ 25 ]. Thus, although this is the first study to explore such disparities in the pediatric orthopaedic population, these trends are likely not unique to pediatric SCHFs and provide insight into the impacts of disparate care with respect to surgical setting.…”
Section: Discussionmentioning
confidence: 99%
“…While there are no previous studies on the socioeconomic patient characteristic differences between inpatient or outpatient care for pediatric SCHF patients, recent studies on total hip and total knee arthroplasties have emphasized that higher SDI scores are associated with inpatient care, alongside African American race, and existence of comorbidities [ 16 , 24 ]. More specifically, a recent study of adult ambulatory surgical care in New York also reported that Black and Hispanic patients had higher odds of receiving inpatient care [ 25 ]. Thus, although this is the first study to explore such disparities in the pediatric orthopaedic population, these trends are likely not unique to pediatric SCHFs and provide insight into the impacts of disparate care with respect to surgical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, findings of underutilization among patients who are Black are not surprising, as they are consistent with other studies of racial disparity in non-cleft populations, which have shown substantial under-utilization of non-emergent surgery among Black populations in the United States (Tompson et al, 2019). This has been attributed, among other factors, to socioeconomic disparity and poorer insurance coverage (Sohn, 2017, Janeway et al, 2020), fewer positive experiences with healthcare as described within social networks (Mota et al, 2012), less explanation of medical options by the operating surgeons (Hausmann et al, 2011), and a general distrust of the medical profession due to historical discrimination (Gamble, 1993). Any combination of these factors may have contributed to underutilization observed in this study, although further study is needed to recognize barriers specific to the Black cleft population.…”
Section: Discussionmentioning
confidence: 99%
“…We focused the analysis on patients who underwent ambulatory arthroscopy, cataract excision, cystoscopy, cholecystectomy, or endoscopy in 2010 to 2018, using Current Procedural Terminology codes that were previously described (eMethods 1 in the Supplement). [2][3][4] Facilities were designated as ASCs or hospital outpatient departments (HOPDs) using data obtained from the SPARCS website.A previously validated socioeconomic advantage score (SES) 5 was calculated at the county and zip code−level using data from the American Community Survey (2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018). This summary score comprised 6 variables that measured wealth, education, and occupation (eMethods 2 in the Supplement).…”
mentioning
confidence: 99%